PHENOMENON OF DEMIKHOV. "Transplantation of vital organs In experiment" (1960). Homoplastic organ transplantation: Transplantation of an additional heart, heart-and-lung transplantation - S. P. Glyantsev (Трансплантология (Москва))
The article (the second of five) reviews the beginning of the Third Chapter from the monograph by V.P.Demikhov "Transplantation of vital organs in the experiment" (M.: Medgiz Publisher, 1960), the chapter covering the issue of homoplastic organ transplantation. The article discusses the results of V.P. Demikhov's work to create the following models: an additional isolated heart, an additional heart with a lung lobe, and a heart in combination with both lungs. Basing on the generally accepted "critical" timing of grafted transplant rejection onset (7th, 14th, or 21th days), Demikhov regarded the graft survival for longer as the fact of the successful engraftment, and every prolongation of the recipient's life with the donor organ as the win over the nature convinced him of the right path chosen. V.P. Demikhov performed the transplantation of the "heart-lungs" complex to simplify the separate anatomical transplantation of these organs and believed that the improvement of surgical methodology and techniques would enable him to achieve their complete engraftment, aiming at further translation the most successful experimental results from the laboratory into the clinical practice.